Aggregation and protein corona formation on gold nanoparticles affect viability and liver functions of primary rat hepatocytes. (September 2016) - Koh, Wee Ling; Tham, Phoebe Huijun; Yu, Hanry; Leo, Hwa Liang; Yong Kah, James Chen
Aim: We examined the impact of aggregation and protein corona formation of gold nanoparticles (AuNPs) on the cytotoxicity, uptake and metabolism, specifically urea and albumin synthesis, of primary rat hepatocytes.Materials & methods: The AuNPs were synthesized via citrate reduction and the human serum protein corona was preformed on the AuNPs. Primary hepatocytes were isolated from male Wistar rats via two-step in situ collagenase perfusion method, and were dosed with both citrate-capped (AuNP-Cit) and protein corona coated AuNPs (AuNP-Cor).Results: The AuNP-Cor showed higher cell uptake and reduced cell viability compared with aggregated AuNP-Cit. Urea and albumin secretions showed AuNP dose dependency. Both AuNP-Cit and AuNP-Cor exerted only an acute effect on the albumin synthesis of hepatocytes with no chronic impact.